Pelayanan Perpustakaan Berbasis Inklusi Sosial di Dinas Perpustakaan dan Arsip Kota Sibolga - Panggabean, Sarah; Ali, M Nasihudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Public libraries should offer inclusive information services that do not discriminate on the basis of age, race, gender, religion, nationality, language, or socioeconomic position. Excluded groups include individuals who are unable to visit the library due to distance, busyness, or lack of time. The purpose of this study was to determine the services and activities of the sibolga city library based on social inclusion. This research uses qualitative methodology, uses a descriptive approach, and uses data collection techniques through interviews, observations, and literature studies. The results showed that the Sibolga City Library and Archives Service has been based on social inclusion seen from the aspects of developing collections that are in accordance with the needs of the community, providing digital libraries, creating digital reading corners (Pocadi), organizing several programs such as musical instrument training, English classes, dish soap making training, creating mobile library services and providing audio-visual rooms for people who want to use these services.